The effect of cyclic torsion on the dislocation structure of drawn mild steel - Maria Teresa Paulino Aguilar; Elaine Carballo Siqueira Corrêa; Waldemar Alfredo Monteiro; Paulo Roberto Cetlin (Materials Research, 2006)
Cold forming is usually associated with the "work hardening" of the material being formed. The work hardening behavior of metals subject to complex processing paths is different from that in monotonic deformation. The results show that, after some initial hardening, there is a possibility that further deformation will cause softening in the material ("work softening"). Recent work showed that cyclic torsion applied to drawn products causes changes in the subsequent tensile behavior of low carbon steel, and that the effect will depend on the previous "history" of the material. For annealed samples, the cyclic torsion leads to an increase in the yield strength, but does not affect the tensile strength and elongation. For the case of previously drawn bars, the cyclic deformation caused a decrease in the yield and tensile strength and an increase in the total elongation. The present paper discusses the dislocation structure changes associated with different strain paths in mild steel.